Cross-Cultural Adaptation of Persian Version of the Motivation to Exercise and Diet in Children Questionnaire: Psychometric Study - Najme Beigi; Rokhsareh Badami (Vesnu Publications, 2021)
Introduction: Childhood obesity is one of the major public health problems of the last century. This study aimed to investigate the validity and reliability of the Persian version of the Motivation to Exercise and Diet in Children (MED-C) questionnaire.Materials and Methods: After receiving formal permission from the developer, the MED-C questionnaire was translated into Persian and back-translated into English. Following approval of back-translated version, this questionnaire along with the Physical Activity Questionnaire for Children (PAQ-C) was filled by 353 Persian-speaking students aged 7-11 years. The construct validity of the scale was measured using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). The convergent validity was determined by the average variance extracted (AVE). The internal consistency and reliability of the scale was then examined using Cronbach's alpha coefficient, and split-half reliability coefficient and composite reliability coefficient, respectively.Results: With EFA, four main factors with an eigenvalue greater than one were extracted, which explained 76.51% of the total variance of the scale. CFA showed that all four factors of the questionnaire, including motivation and need for exercise, motivation and need for diet and nutrition, had a high correlation with the whole questionnaire, and these factor loadings were significant at the level of 0.001. The reliabilities obtained in the questionnaire were higher than 0.7 and acceptable. A significant correlation was found between physical activity and dimensions of MED-C (P = 0.01).Conclusion: The Persian version of the MED-C questionnaire seems to be a valid and reliable tool for measuring the motivation for physical activity and diet in Iranian children.